Air Quality Monitoring Technology and Its Benefits for Public Health: A Review - Pongsigala, Gracia Indri Agustin; bawia, Muhammad Anugrah; Semu, Margaretha (Journal of Epidemiology and Health Science, 2026)
Background: Urban and industrial air pollution releases harmful substances that threaten human health. Fine particulate matter (PM1.0, PM2.5, PM10) is associated with respiratory and cardiovascular diseases, while gases such as NOx and CO disrupt oxygen transport and increase poisoning risk. The World Health Organization reports that 99% of the global population is exposed to polluted air, contributing to approximately 6.5 million premature deaths annually. Air pollution also affects neurological and reproductive health, increasing risks of developmental disorders, neurodegenerative diseases, and mental health problems. Objective: This study aims to describe the development of air quality monitoring technologies for detecting pollution. Methods: A descriptive Systematic Literature Review (SLR) was conducted using PRISMA guidelines, analyzing national and international publications from databases such as Google Scholar and ResearchGate. Results: IoT-based monitoring systems and digital sensors effectively measure pollutants in real time with high accuracy. These technologies support early warning systems, policy-making, and public awareness. Conclusion: IoT-based air quality monitoring offers an efficient solution for improving environmental health, although challenges remain in implementation and accessibility. Keywords: Air pollution, public health, technology, monitoring, IoT.